2010
DOI: 10.1055/s-0030-1248283
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cardiopulmonary Exercise Testing Protocol and Resting VO2Assessment on %HRmax, %HRR, %VO2maxand %VO2R Relationships

Abstract: The findings of previous studies that investigated the strength of the relationships between the percentages of maximal heart rate (%HRmax), heart rate reserve (%HRR), maximal oxygen uptake (%VO2max), and oxygen uptake reserve (%VO2R) have been equivocal. This inconsistency between studies could largely be due to differences in methodology. The purpose of this study was therefore to determine whether different VO2max test protocols and resting VO2 assessment influence the relationships between the %HRmax, %HRR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 45 publications
2
60
1
3
Order By: Relevance
“…Consequently, whether these results are to be used for exercise prescription, we would be underestimating the intensity of the effort, which is not in accordance with the ACSM recommendations (ACSM, 2013). However, these results differ when equations are used to predict HRmax (Cunha et al, 2010) as previously demonstrated by Caputo, Cozzensa da Silva and Rombaldi (2012), in which the authors recommend avoiding the equations because they restrict the HRmax. So far, there is no appropriate formula for this estimation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Consequently, whether these results are to be used for exercise prescription, we would be underestimating the intensity of the effort, which is not in accordance with the ACSM recommendations (ACSM, 2013). However, these results differ when equations are used to predict HRmax (Cunha et al, 2010) as previously demonstrated by Caputo, Cozzensa da Silva and Rombaldi (2012), in which the authors recommend avoiding the equations because they restrict the HRmax. So far, there is no appropriate formula for this estimation.…”
Section: Discussionmentioning
confidence: 84%
“…For adults, the cardiorespiratory exercise recommendation is already defined (Cunha et al, 2010;Garber et al, 2011). To our knowledge there is no data for adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VO 2 in both conditions converting it into a percentage of VO 2 to be correlated between a percentage of VO 2 and a heart rate reserve (%HRR). 10 In addition, using a patient monitor (BSM-2401, Nihon Kohden, Tokyo, Japan), we recorded the ECG consecutively and counted an interval every one beat (R splinter-R splinter) for 30 seconds by calculating the value every minute so as to find the heart rate (HR) per minute. HR was calculated as the mean during the two minutes before the end of the measurement and was converted into %HRR.…”
Section: Measurementmentioning
confidence: 99%
“…HR was calculated as the mean during the two minutes before the end of the measurement and was converted into %HRR. 10 We measured the perceived exertion using the OMNI scale (eleven levels). 11 We recorded it on the incremental exhaustion tests only with regard to the whole body; for both conditions of the experiment, perceived exertion was recorded for the whole body, upper limbs, and lower limbs.…”
Section: Measurementmentioning
confidence: 99%